Enhancing the role of fiscal policy in New Zealand's macroeconomic stabilisation - Jenna Bernstein; Ben Gaukrodger; Oscar Parkyn (New Zealand Government, The Treasury, 2024)
This paper considers the role of fiscal policy in New Zealand's macroeconomic stabilisation. New Zealand's macroeconomic framework is characterised by an institutional arrangement whereby monetary policy has the primary responsibility for macroeconomic stabilisation. In contrast, fiscal policy is generally oriented around medium-term structural goals and debt sustainability. There is a need to reassess the role of fiscal policy in the wake of COVID-19 and structural trends. As has been the experience over recent economic cycles, fiscal policy may need to play a significant role in macroeconomic stabilisation in the future, especially if monetary policy becomes constrained by the effective lower bound on interest rates. This paper examines the high-level options for improving the effectiveness of counter-cyclical fiscal policy, including strengthening the automatic stabilisers, counter-cyclical discretionary policies and developing "semi-automatic" stabilisers. There is a need to consider fiscal institutions and administrative capacity to implement stabilisation policy effectively and maintain debt sustainability.
Keywords: E61; E62; 330; Fiscal policy; stabilisation; automatic stabilisers; semi-automatic stabilisers; discretionary fiscal policy